Hematological, hormonal and fitness indices in youth swimmers: Gender-related comparisons - Cai, G.; Qiu, C.; Chen, S.; Pan, Q.; Shen, X.; Kang, J. (Journal of Human Kinetics, 2019)
This study objective was to evaluate gender differences in hematological, hormonal and fitness variables among youth swimmers and to explore relationships between erythrocyte indices and aerobic and anaerobic capacity. 137 girls and 171 boys participated in the study and were divided into three groups based on their training experience. Blood samples were obtained to determine red blood cell counts, hemoglobin concentration, hematocrit, and plasma erythropoietin and testosterone levels. VO2max was assessed using a submaximal cycle protocol. 76 girls and 102 boys also undertook a Wingate test to determine their peak anaerobic power. Boys had higher (p < 0.05) means than girls for all hematological variables except for erythropoietin and these variables demonstrated an increase with training in boys. The average VO2max in l·min-1 and peak anaerobic power in watts were also higher in boys (2.91 ± 0.08 and 547 ± 28, respectively) than girls (2.25 ± 0.07 and 450 ± 26, respectively). Modest but significant (p < 0.05) correlations were found between VO2max and red blood cell counts (r = 0.252), hemoglobin concentration (r = 0.345), or hematocrit (r = 0.345) and between peak anaerobic power and red blood cell counts (r = 0.304), hemoglobin concentration (r = 0.319) or hematocrit (r = 0.351). This study revealed relatively lower yet age- and gender-appropriate hematological, hormonal and fitness indices in youth swimmers. The gender-related differences in erythrocyte indices seem unrelated to erythropoietin and may be explained by the higher testosterone levels seen in boys. Given their correlation to both aerobic and anaerobic capacity, erythrocyte indices may be used as part of talent identification for sports.